The has-miR-526b binding-site rs8506G>a polymorphism in the lincRNA-NR_024015 exon identified by GWASs predispose to non-cardia gastric cancer risk. - Qiu-Hong Fan; Rong Yu; Wei-Xian Huang; Xi-Xi Cui; Bing-Hui Luo; Li-Yuan Zhang (PLoS ONE)
Gastric cancer including the cardia and non-cardia types is the second frequent cause of cancer-related deaths worldwide. A subset of non-cardia gastric cancer genetic susceptibility loci have been addressed among Asian through genome-wide association studies (GWASs). This study was to evaluate the effects of single nucleotide polymorphisms (SNPs) of long intergenic non-coding RNAs (lincRNAs) on non-cardia gastric cancer susceptibility in Chinese populations. We selected long intergenic noncoding RNAs (lincRNAs) located in non-cardia gastric cancer risk-related loci and identified 10 SNPs located within lincRNA exonic regions. We examined whether genetic polymorphisms in lincRNAs exons are associated with non-cardia gastric cancer risk in 438 non-cardia gastric cancer patients and 727 control subjects in Chinese populations using logistic regression. Functional relevance was further examined by biochemical assays. We found that lincRNA-NR_024015 rs8506AA carrier was significantly associated with risk of non-cardia gastric cancer (adjusted odds ratio [OR] = 1.56, 95%CI = 1.03-2.39, compared with the rs8506 AG or GG genotype. Further stratification analysis showed that the risk effect was more pronounced in subgroups of smokers (P = 0.001). Biochemical analysis demonstrated that the G to A base change at rs8506G>A disrupts the binding site for has-miR-526b, thereby influencing the transcriptional activity of lincRNA-NR_024015 and affecting cell proliferation. Our present study established a robust association between the rs8506G>A polymorphism in the lincRNA-NR_024015 exon and the risk of non-cardia gastric cancer.